Fine particulate matter exposure during childhood relates to hemispheric-specific differences in brain structure. (October 2020) - Cserbik, Dora; Chen, Jiu-Chiuan; McConnell, Rob; Berhane, Kiros; Sowell, Elizabeth R.; Schwartz, Joel; Hackman, Daniel A.; Kan, Eric; Fan, Chun C.; Herting, Megan M.
Highlights: Largest study to date on fine particulate matter (PM2.5 ) and brain in children. Individual residential PM2.5 exposure assigned for 10, 343 U.S. children at 21 sites. PM2.5 associated with regional- and hemisphere-specific brain differences. PM2.5 was not associated with NIH Toolbox performance. Findings were similar in both boys and girls. Abstract: Background: Emerging findings have increased concern that exposure to fine particulate matter air pollution (aerodynamic diameter ≤ 2.5 μm; PM2.5 ) may be neurotoxic, even at lower levels of exposure. Yet, additional studies are needed to determine if exposure to current PM2.5 levels may be linked to hemispheric and regional patterns of brain development in children across the United States. Objectives: We examined the cross-sectional associations between geocoded measures of concurrent annual average outdoor PM2.5 exposure, regional- and hemisphere-specific differences in brain morphometry and cognition in 10, 343 9- and 10- year-old children. Methods: High-resolution structural T1-weighted brain magnetic resonance imaging (MRI) and NIH Toolbox measures of cognition were collected from children at ages 9–10 years. FreeSurfer was used to quantify cortical surface area, cortical thickness, as well as subcortical and cerebellum volumes in each hemisphere. PM2.5 concentrations were estimated using an ensemble-based model approach and assigned to each child's primary residential address collected at the study visit. We used mixed-effects models to examine regional- and hemispheric- effects of PM2.5 exposure on brain estimates and cognition after considering nesting of participants by familial relationships and study site, adjustment for socio-demographic factors and multiple comparisons. Results: Annual residential PM2.5 exposure (7.63 ± 1.57 µg/m 3 ) was associated with hemispheric specific differences in gray matter across cortical regions of the frontal, parietal, temporal and occipital lobes as well as subcortical and cerebellum brain regions. There were hemispheric-specific associations between PM2.5 exposures and cortical surface area in 9/31 regions; cortical thickness in 22/27 regions; and volumes of the thalamus, pallidum, and nucleus accumbens. We found neither significant associations between PM2.5 and task performance on individual measures of neurocognition nor evidence that sex moderated the observed associations. Discussion: Even at relatively low-levels, current PM2.5 exposure across the U.S. may be an important environmental factor influencing patterns of structural brain development in childhood. Prospective follow-up of this cohort will help determine how current levels of PM2.5 exposure may affect brain development and subsequent risk for cognitive and emotional problems across adolescence.